Правові засади регулювання державної гендерної політики в Україні - Перевалова, Людмила Вікторівна; Гаряєва, Ганна Михайлівна (НДІ правового забезпечення інноваційного розвитку НАПрН України, 2021)
статті проведено дослідження державної політики України в сфері гендерної рівності. Проаналізовано міжнародні норми та діюче українське законодавство в сфері забезпечення рівності прав чоловіків і жінок, ліквідації всіх форм дискримінації щодо жінок, протидії домашньому насильству. Автори розглядають як позитивні, так і негативні сторони державної гендерної політики; обґрунтовують необхідність подальшого вдосконалення діючого законодавства, приведення його у відповідність до міжнародних правових стандартів.

Problem setting. Gender policy today is one of the decisive factors in building civil society, reaching consensus between different branches of government, the successful implementation of democratic reforms in Ukraine, its integration into the European Union. The observance of gender equality in the state demonstrates how civilized and democratic it is. The purpose of this article is a general study of the main directions of state gender policy, analysis of international norms in the field of gender equality and compliance of current Ukrainian legislation with international legal standards. Analysis of recent researches and publications. Issues of legal support for gender equality in Ukraine are studied by scientists in various aspects, as indicated by the scientific works of Kobelyanska L., Hrytsyak N., Hrytsai I., Grabovska I., Melnyk T., Honyukova L., Pedchenko N., Kresina I. and others. Article’s main body. However, some aspects related to further improvement of the state gender policy, bringing the current legislation in line with international and regional legal standards remain unresolved. The implementation of these tasks has not only theoretical but also significant practical significance and, accordingly, requires further research. Problems of studying the state policy of Ukraine in the field of gender equality remain relevant, as evidenced by the analysis of international norms and current Ukrainian legislation in the field of equality of rights of men and women, elimination of all forms of discrimination against women, combating domestic violence. The article considers both the positive and negative aspects of the state gender policy; the necessity of further improvement of the current legislation, bringing it in line with international legal standards, which is especially important in connection with the European integration processes of Ukraine, is substantiated. Conclusions and prospects for development. Thus, it should be noted that gender policy remains an important area of public policy, but unfortunately, despite significant advances in gender equality, public policy is reduced to such separate areas as assistance to families with children, social protection of women, protection of women in sphere of labor, etc. These areas of state social policy are very important, but they are not exhaustive. In addition, the legal framework for state gender policy needs to be further improved. Not all legal documents are perfect, unambiguous and can be fully applied in practice and therefore need further refinement. The Law on Ensuring Equal Rights and Opportunities for Women and Men, adopted in 2005, needs to be updated because it does not meet modern needs. In addition, Ukraine lacks a National Strategy in the field of gender equality, which would promote the further development of the principle of gender integration in all spheres and branches of public administration. The problem of equal rights for women and men in a democratic society is proclaimed as one of the main tasks in solving today’s social problems.
Legal principles of regulation of state gender policy in Ukraine
Keywords: гендерна рівність; гендерна політика; права жінок; дискримінація; насильство; gender equality; gender policy; women's rights; discrimination; violence